Les artistes de l’eau - Chiara Santini (Projets de Paysage, 2009)
The analysis of the professions and the technical skills developed in the realisation of pleasure gardens lead, during the last years, to new opportunities of research investigation in the field of landscape and garden history. Based on this new study trend, this article reviews the art of managing the waters in the gardens of the classical period through the analysis of the training, the savoir-faire and the daily work of Versailles hydrant men during the age of Louis XIV. Based on archived documents, correspondence, and architecture and hydraulic treaties, this research aims to contribute to studies on garden arts evolution and on the professions related to it during the modern era.